Design and packaging of a compact circularly polarised planar antenna for 2.45‐GHz RFID mobile readers. Issue 13 (26th July 2019) - Gautam, Anil Kumar; Farhan, Mohd.; Agrawal, Niraj; Rambabu, Karumudi
Abstract : In this study, a novel design and packaging of miniaturised planar microstrip antenna with circular polarisation (CP) that is suitable for 2.45‐GHz radio‐frequency identification (RFID) applications is proposed. The circular polarisation is realised by truncating the corners of the left to right diagonal and 76% of miniaturisation is achieved by incorporating two slots in each of the four directions and one at the centre of the square‐shaped radiator. This type of miniaturisation method is known in the literature but combining with CP radiation is a novel approach. The radiator of the designed antenna has a compact size of 19.6 × 19.6 mm 2 with an overall size of the antenna 30 × 30 × 1.6 mm 3, and this technique offers 76% miniaturisation in antenna size. Finally, a prototype antenna is fabricated and experimentally characterised to verify the design concept as well as to validate the simulation results. The designed antenna achieves measured return loss bandwidth of around 80 MHz (2.42– 2.5 GHz) and axial ratio bandwidth of 21 MHz (2.447–2.468 GHz). The proposed antenna is a good candidate for RFID mobile reader applications as it shows a good radiation performance, when it is installed in various types of housing.